THE USE OF NOMOGRAMS FOR DETERMINING THE OUTER RAIL AND ALLOWED SPEEDS IN CURVES - Rybkin, V. V.; Patlasov, O. M.; Vlasova, A. V. (Science and Transport Progress, 2003)
The algorithm for building a nomogram is considered in this paper. The nomogram is used to determine the outer rail lifting and the permissible rolling stock speeds at track curves. Table processor Microsoft Excel was used to build the nomogram. The example is given to use the nomogram the for specific data.